When income inequality reduction meets green transition: pay gap and green innovation in China - Tang, Pengcheng; Wang, Guolin; Liu, Xuan; Wang, Junyu (Journal of environmental planning and management, 2025)
While existing research at the national/regional and individual levels often emphasizes the compatibility between income inequality reduction and green transition, our study, based on the incentive alignment theory, argues that a certain level of pay gap can encourage executives to exert more management efforts on navigating the organizational change brought about by green innovation. Using a sample of Chinese public firms from 2012 to 2018, our empirical findings, based on ordinary least squares, the Heckman selection model and instrumental variable regression, demonstrate a positive impact of a pay gap on green innovation, particularly on green patents that require more management efforts due to the higher inventive step. Meanwhile, this positive effect is enhanced by executives with backgrounds in both R&D and environmental protection, as well as stronger regulatory pressures and financial resources. However, an excessive pay gap would limit the enthusiasm of employees with high bargaining power and a low sense of belonging to participate in green innovation. Our paper not only advances the understanding of how to promote green innovation, but also has significant practical implications for balancing green transition and pay equity in China and possibly in other countries where tradeoffs exist between these two domains.